Evaluations of Antioxidant Effects of Selected Medicinal Plant Extracts Claimed to Treat Kidney Stone Disease - Alelign, Tilahun; Debella, Asfaw; Petros, Beyene (Free Radicals and Antioxidants)
Introduction: Free radicals are capable of inducing oxidative damage, which causes various human diseases. However, antioxidants reduce the risk of diseases related to reactive oxygen species. Medicinal plants such as Achyranthes aspera leaves, Satureja punctata aerial parts, Aloe pulcherrima gel, Gomphocarpus fruticosus leaves and Commiphora myrrha resins were claimed to treat various ailments including urolithiasis in Ethiopia. Objectives: This study was intended to determine phytochemicals and antioxidant activities of the aforementioned plants. Materials and Methods: Plants were collected and the aqueous crude extracts were prepared. Phytochemicals were screened qualitatively and DPPH(2,2-diphenyl-1-picrylhydrazyl) radical scavenging assay was measured at 517nm using UV-Vis spectrophotometry. Data were analyzed statistically using one-way ANOVA, Dunnett’s comparison test of the Graph Pad Prism version 6. Results: The plant extracts exhibited various phytochemicals such as phenols, flavonoids and tannins, while these were absent in C. myrrha. Steroids and terpenoides were absent in A. pulcherrima and G. fruticosus extracts, respectively. DPPH scavenging capacities of S. punctata, G. fruticosus, A. pulcherrima and A. aspera aqueous extracts were 92.3%, 81.6%, 72.3% and 54.9%, respectively compared to control (Ascorbic acid) showed 87.6%, 94.5%, 92.3% and 95.6%, respectively at inhibitory concentrations of 0.20 mg/ml, 0.78 mg/ ml, 3.13 mg/ml and 12.5 mg/ml, respectively. The IC50 antioxidant values of S. punctata, A. pulcherrima, G. fruticosus, and A. aspera extracts were 0.01 ±0.003 mg/ml, 0.42 ±0.047 mg/ml, 1.64 ±0.147 mg/ml, and 13.51 ±1.08 mg/ml, respectively compared to Ascorbic acid (0.03 ±0.007 mg/ml). Conclusion: The phytoconstituents in S. punctata aqueous extract has the best capability to scavenge DPPH free radicals. Future characterizations of compounds responsible for the antioxidant activities will be required.
Keywords: Antioxidant activity; DPPH; Free radicals; Medicinal plants; Phytochemicals